Analisis Pembelajaran Sejarah Siswa Kelas X SMA Negeri 11 Medan Berbasis Outing Kelas di Museum Negeri Sumatera Utara - Nababan, Surya Aymanda; Vira Yunita; Saragih, Ridho Gilang Amalsyah (Medan Resource Center, 2023)
The objectives of this research include the importance of developing effective and interesting history learning methods as well as the need to understand the impact of history learning outside the classroom, especially in museums. In this approach, this research discusses the concept of historical literacy and its benefits in the context of history learning. This research uses data collection techniques involving surveys, observations, and interviews with class x students, teachers, and museum staff. The research results reveal a number of challenges faced in implementing outing class-based history learning, such as a lack of resources and limited time. However, this research also identified its benefits in increasing students' understanding of history and motivating them to study more deeply. The results of this research can provide guidance for educators and policy makers in developing more varied and interesting history learning methods. In addition, this research highlights the role of museums in history education and the importance of utilizing cultural and historical resources in the surrounding environment to increase students' historical understanding. The